Elasticity Detection: A Building Block for Internet Congestion Control - Goyal, Prateesh; Narayan, Akshay; Cangialosi, Frank; Narayana, Srinivas; Alizadeh, Mohammad; Balakrishnan, Hari (ACM SIGCOMM, 2022)
This paper introduces a new metric, "elasticity," which characterizes the nature of cross-traffic competing with a flow. Elasticity captures whether the cross traffic reacts to changes in available bandwidth. We show that it is possible to robustly detect the elasticity of cross traffic at a sender without router support, and that elasticity detection can reduce delays in the Internet by enabling delay-controlling congestion control protocols to be deployed without hurting flow throughput. Our results show that the proposed method achieves more than 85% accuracy under a variety of network conditions, and that congestion control using elasticity detection achieves throughput comparable to Cubic but with delays that are 50–70 ms lower when cross traffic is inelastic.